Economic and social responsibility of financial auditing: a new dimension - Borzán, Anita; Lentner, Csaba; Szigeti, Cecília (REGIONAL AND BUSINESS STUDIES, 2011)
The current financial crisis has a classic three-dimensional structure of responsibility. Creditor banks must ensure the money supply, aggregate demand for loans to households in debt, and monetary authorities (supervisors, governments). We consider it essential that the auditors’ and any operator’s responsibility extend not only to the economics of profits and losses but also to society, be it local, national, or global. As many banks are global operators, financial auditing must also have a global dimension. In the fourth year of the sub-prime crisis, auditors’ responsibilities have shifted to a new dimension. In light of this, our presentation is mainly focused in the European Union’s Green Paper titled, „The Audit Policy: Lessons from the Crisis.” This report recommends more transparency and encourages a return to substantial survey. In it, auditors are exhorted to professional scepticism. It is necessary to enhance dialogue between auditors and banking regulatory authorities. Audit of European reform, however, may not be adequately effective in global markets, since international companies and global operators are not subject to it while outside the EU. As such, we will present examples of related legislation from overseas, particularly the now-completed inquiry report of the U.S. Congress. There is no doubt that responsibility for auditing companies has exceeded the corporate economic area and national boundaries. International economic performance and confidence in the wide international markets has begun to show the effects of new auditing policies. This presentation is about the content and quality challenges involved in changing auditors. The global economy is a global challenge to which all auditors must adjust if they are to do their job of strengthening and securing global markets. Keywords: CSR of banks, subprime crisis, auditing, EU Green Paper, overseas practice